A Picture's worth a thousand words interpreting visual information. (Center for Humanities, 1977)
Concerns the information to be gained from pictures. Stresses photography as a seemingly objective, but very selective view of reality. Introduces special language designed to communicate factual information, maps, charts and graphs.